Disaster risk management for critical infrastructure: a services-based viewpoint. Issue 2 (5th May 2009) - Zobel, Christopher W.; Martin II, James R.; Olgun, C. Guney
It is necessary to protect critical infrastructure and key resources from the effects of a disaster in order to maintain continuity of both public services and private enterprise. Since many of the critical resources are themselves privately owned and operated, however, they are often subject to the same market pressures that force businesses to concentrate on improving the efficiency of their operations at the possible expense of guarding against potential disruptions to those operations. Under these circumstances, the process of designing an effective (and acceptable) disaster mitigation plan for critical infrastructure resources requires a shared understanding of both the business aspects and the technical aspects of different mitigation alternatives. This paper examines the decision-making process behind such disaster mitigation planning from a services standpoint and discusses how taking such a viewpoint can provide a more effective approach to sustainable disaster risk reduction.